PENGEMBANGAN MEDIA PEMBELAJARAN DIORAMA EKOSISTEM SUNGAI BERBASIS ECO-HACK TERHADAP MINAT BELAJAR SISWA KELAS X MA AL QODIRI JEMBER - Dewi Antika Khasanah; Nanda Eska Anugrah Nasution (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The low learning interest of students in river ecosystem material at MA Al-Qodiri Jember is caused by monotonous learning processes and limited use of concrete learning media. Therefore, an Eco-Hack-based diorama learning media was developed by utilizing environmentally friendly materials and presenting a real visualization of river ecosystems. This study aimed to describe the validity, practicality, and effectiveness of the Eco-Hack-based river ecosystem diorama learning media in improving the learning interest of tenth-grade students at MA Al-Qodiri Jember. This study used a Research and Development (R&D) method with the ADDIE development model consisting of Analysis, Design, Development, Implementation, and Evaluation stages. Data collection techniques included interviews, questionnaires, and documentation. The effectiveness test used a one-group pretest-posttest design. The results showed that the developed learning media was valid, with media expert validation of 80.21%, material expert validation of 85%, language expert validation of 93.33%, and practitioner expert validation of 93.75%. The media was also considered very practical based on student response results of 91% in the small group trial and 91.7% in the large group trial. In addition, the media was proven sufficiently effective in increasing students’ learning interest, indicated by a Sig. value of 0.000 < 0.05 and an N-Gain score of 0.5105 or 51.05%, categorized as moderately effective. Therefore, the Eco-Hack-based diorama learning media is feasible for use in Biology learning on river ecosystem material.